Inicjatywy edukacyjne jako sposób zatrudnienia nauczyciela przedszkolnego i wzmocnienie jego wizerunku - Alezra Fani, Fani (Studia Edukacyjne, 2019)
The recognition of the importance of early childhood education is steadily increasing. Many reports published in Israel and around the world address the tremendous and critical impact of this age on the individual and on society. In contrast, the professional image of the preschool teacher in Israel is low, as in many countries. The professional image influences the choice of the teaching profession and the acceptance conditions in the teacher training colleges. This article addresses unique educational pedagogical initiatives that incorporate advanced technology and innovative teaching methods that may have positive influence on the preschool teacher’s image and serve as a focus for community involvement, positive advertising, and empowerment of the children and the preschool. Therefore, the aim of the article is to emphasize the importance of the educational initiatives and their direct and indirect impact on the preschool image and the parents’ satisfaction with the preschool activity, to encourage the preschool teachers who do not yet integrate educational initiatives in their activity to do so, and to emphasize the importance of the involvement of the parents and the community in the preschool pedagogical activity. This research was performed through the distribution of questionnaires to the parents in the preschools where educational initiatives were held and in the preschools where these initiatives were not held and the examination of the parents’ satisfaction.